2022
DOI: 10.3390/agriculture12081159
|View full text |Cite
|
Sign up to set email alerts
|

Why “Say One Thing and Do Another” a Study on the Contradiction between Farmers’ Intention and Behavior of Garbage Classification

Abstract: How to protect the ecological environment is an important international issue for achieving the sustainable development goals. Using survey data of 2628 farmers in 52 administrative villages in 13 prefecture-level cities of the China Land Economic Survey in 2020, probit and multinomial logistic regression models were used to explore the influence of social capital on farmers’ willingness, behavior and the transformation between willingness and behavior. The results show that: (1) The consistency between farmer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
2

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 50 publications
(71 reference statements)
1
5
2
Order By: Relevance
“…Our study results indicate that the awareness by community residents of the necessity of establishing SJLNNR and the environmental improvement effect of SJLNNR are two factors that would both increase the deviation, which is different from previous research on pro-environmental behaviors (Vodouhê et al, 2010;Kuang and Lin, 2021;Li et al, 2021;Zhou et al, 2022), These unexpected results can be attributed to inadequate ecological compensation. During this survey, we found that the feelings of community residents regarding SJLNNR were complex.…”
Section: Inadequate Ecological Compensation Is the Direct Triggercontrasting
confidence: 99%
See 2 more Smart Citations
“…Our study results indicate that the awareness by community residents of the necessity of establishing SJLNNR and the environmental improvement effect of SJLNNR are two factors that would both increase the deviation, which is different from previous research on pro-environmental behaviors (Vodouhê et al, 2010;Kuang and Lin, 2021;Li et al, 2021;Zhou et al, 2022), These unexpected results can be attributed to inadequate ecological compensation. During this survey, we found that the feelings of community residents regarding SJLNNR were complex.…”
Section: Inadequate Ecological Compensation Is the Direct Triggercontrasting
confidence: 99%
“…Awareness of the necessity of establishing SJLNNR by community residents is a direct influencing factor at the surface level. Furthermore, the deep- The results from our study show that the number of resident members is a deep-rooted influencing factor that significantly decreases the deviation, which varies from the research finding of Zhou et al (2022). This may be closely linked to the rural hollowing, which means that numerous educated young and middle-aged agricultural laborers in traditional agricultural areas transfer to non-agricultural sectors in urban areas during the process of rapid urbanization and industrialization in China (Cui et al, 2011).…”
Section: Hierarchical Structure Of These Influencing Factorscontrasting
confidence: 66%
See 1 more Smart Citation
“…For example, Liu et al [31] found that using the Internet can positively influence farmers' willingness to classify garbage, though different Internet types on farmers' willingness to classify garbage is heterogeneous. Zhou et al [32] and Xu et al [22] also found that the use of the Internet has significantly improved farmers' willingness and action on waste classification.…”
Section: Introductionmentioning
confidence: 99%
“…With the rapid development of digital technologies such as the internet, big data, artificial intelligence, cloud computing and blockchain, they are profoundly influencing and changing the way humans produce, live and govern ( 18 20 ). From the perspective of digitally empowered governance approaches, digital governance is a governance model in which the government applies digital technology between the government and residents, enterprises and other subjects, as well as in the internal operation of the government to achieve the purpose of simplifying the process of handling public affairs and achieving democratic governance ( 21 ).…”
Section: Introductionmentioning
confidence: 99%